CERPEN LESUNG PIPIT KARYA EKA KURNIAWAN: KONSEPSI KEPERAWANAN SEBAGAI STRATEGI PERLAWANAN - Marsten Lihardo Tarigan; Fiona Djunita Natalia Luhulima; Yulia Putri Paradida (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
One of the conceptions held by society today is virginity. This conception of virginity has become an issue of sexuality, which is often an important discussion in society. Virginity is often regarded as the standard of chastity for a woman. The short story "Lesung Pipit" by Eka Kurniawan describes the complexities of women's lives and the values and conceptions that encompass them. Literary works that explore the issues of women and sexuality often show a picture of their resistance to existing conceptions and the inequality experienced by women. This study aims to discuss the conception of virginity, which has the potential to be a form of resistance to the reinforcement of stereotypes of women through characters in short stories, with a feminist literary criticism approach. The results of this study show that in depicting the strategy of resistance and the conception of virginity in short stories, the female characters want to state that virginity, which is considered a standard value that weakens women, can also be used as a strength and strategy to fight back. Furthermore, there is also a description of the confirmation of the conception of virginity in the short story. The values and standards that are attached to women are not only owned and believed by men, but also by women.